Diagrams in mathematics: To draw or not to draw? - Vimolan Mudaly (Perspectives in Education, 2012)
This paper describes the use of diagrams as self-explanatory tools. It considers the use of diagrams, in general, and more specifically, examines research that is currently being undertaken in the broad field of visualisation. The research participants referred to in this article were Advanced Certificate of Education students and the paper attempts to analyse their responses to questions based on simple area problems in mathematics. The outcome of this research underscores the strategic use of diagrams when dealing with problem solving. While this is an ongoing research project, the paper attempts to capture the current status of research on the use of diagrams.